Adverse Experiences in Early Childhood and Emotional Behavioral Problems Among Chinese Preschoolers: Psychological Resilience and Problematic Media Use - Yantong Zhu; Liu Yang; Gengli Zhang (Behavioral Sciences, 2025)
Adverse childhood experiences (ACEs) in early childhood may increase the risk of emotional behavioral problems (EBPs); however, few studies have explored the longitudinal effect of ACEs in early childhood on later EBPs and their underlying mechanisms. This study examined the serial mediating role of psychological resilience (PR) and problematic media use (PMU) in the relationship between ACEs in early childhood and EBPs. Participants included 534 three-year-old children (mean age of 33.29 years, SD = 3.97) and their parents from Wuhu, China. The parents completed online questionnaires measuring children’s ACEs, PR, and demographic information in September 2022 (Time 1), children’s PMU in September 2023 (Time 2), and EBPs in September 2024 (Time 3). Macro Process 6 was used to test the serial mediating effects of PR and PMU. A total of 5000 bootstrap samples were used to estimate the 95% confidence intervals. The results revealed that ACEs in early childhood did not directly predict EPBs. PR (b = 0.132 (95% CI [0.051, 0.221])) mediated the relationship between ACEs and children’s EBPs. PR and PMU also played a serial mediating role in the association of ACEs and children’s EBPs (b = 0.026, 95% CI [0.008, 0.054]). Our findings highlight the importance of improving PR and addressing PMU when designing interventions targeting Chinese preschoolers exposed to ACEs.